Analysis of the Implementation of EMR Integration into the SATUSEHAT Platform at X Hospital - Martinadewi, Allita; Gunawan, Erix (Greenation Publisher & Yayasan Global Research National, 2024)
The implementation of EMR integration into the SATUSEHAT Platform at X Hospital has yet to be fully integrated. This research aims to analyze the implementation of electronic medical record integration into the SATUSEHAT Platform at X Hospital. This type of research is qualitative with a descriptive approach and uses Edwards III policy implementation theory. Using purposive sampling techniques, research data was collected through interviews with four informants and observations. The validity of the data was tested using source triangulation and technique triangulation. The research results show that X Hospital has successfully integrated 93.5% of its data with SATUSEHAT, while the remaining 6.5% have metadata variable inconsistencies and need adjustments to be integrated with SATUSEHAT. The main conclusion shows that the bureaucratic structures related to SOP in X Hospital need to be fixed, and there is a mismatch in the National ID Number in the metadata variable between X Hospital's Management Information System and the Ministry of Health Republic of Indonesia. Therefore, X Hospital needs to evaluate and improve the metadata variables of the EMR system to be appropriate and facilitate data interoperability.